EFISIENSI USAHATANI PAPRIKA (Capsicum annuum L.) - Dirham, Maqfirah Ramadhani; Nadja, Rahmawaty A.; Mahyuddin, Mahyuddin; Rukmana, Didi; Heliawaty, Heliawaty (Agros Journal of Agriculture Science, 2023)
This research aims to analyze the factors that influence paprika production, analyze the technical and economic efficiency of the use of production factors in paprika farming. The respondents in this research were Buluballea paprika farmers. The method used is quantitative descriptive using multiple linear regression with the Cobb-Douglas production function model as well as technical and economic efficiency analysis. The research results show that the input factors of labor, seeds, AB mix fertilizer, husk charcoal, and pesticides simultaneously and partially have a significant effect on paprika production with the RTS yield scale being on the Increasing Return to Scale business scale. Furthermore, production input factors, namely labor, seeds, AB mix fertilizer, husk charcoal, and pesticides have a positive and significant effect on paprika production. The results of the technical efficiency analysis of the production factors used are labor, paprika seeds, AB mix fertilizer, husk charcoal and pesticides which are not technically efficient. Where all production factors need to be reduced. The results of the analysis of the economic efficiency of paprika farming show that production factors that are inefficient are seeds, AB mix fertilizer, husk charcoal and pesticides, so they need to be added to achieve optimal conditions, while production factors that are inefficient are labor, so they need to be reduced to achieve optimal conditions. Keywords : Cobb-Douglas, Farming Efficiency, Paprika INTISARIPenelitian ini bertujuan menganalisis faktor-faktor yang mempengaruhi produksi paprika, menganalisis efisiensi teknis      dan ekonomi dari penggunaan faktor produksi usahatani paprika. Responden dalam penelitian ini adalah petani paprika Buluballea. Metode yang digunakan adalah deskriptif kuantitatif menggunakan regresi linier berganda dengan model fungsi produksi Cobb-Douglas serta analisis efisiensi teknis dan ekonomi. Hasil penelitian menunjukkan faktor  input tenaga kerja, benih, pupuk AB mix, arang sekam, dan pestisida secara simultan dan parsial berpengaruh signifikan terhadap produksi paprika dengan keadaan skala hasil RTS berada pada  skala usaha Increasing Return to Scale. Selanjutnya, faktor input produksi yaitu tenaga kerja, benih, pupuk AB mix, arang sekam, dan pestisida berpengaruh positif dan signifikan terhadap   produksi paprika. Hasil analisis efisiensi teknis faktor produksi yang digunakan yaitu tenaga kerja, benih paprika, pupuk AB mix, arang sekam, dan pestisida tidak efisien secara teknis. Dimana seluruh faktor produksi perlu dikurangi. Hasil analisis efisiensi ekonomi usahatani paprika menunjukkan faktor produksi yang belum efisien yaitu benih, pupuk AB mix, arang sekam, dan pestisida sehingga perlu ditambah untuk mencapai kondisi optimal, sedangkan faktor produksi yang tidak efisien yaitu tenaga kerja, sehingga perlu dikurangi untuk mencapai kondisi optimal. Kata Kunci : Cobb-Douglas, Efisiensi Usahatani, Paprika